Use of Fluoridated Dentifrices among Children: Are We in the Right Direction? - Kapur, Aditi; Thakur, J. S.; Gauba, K.; Goyal, A.; Mohit, K.; Manoj, J. (Annals of the National Academy of Medical Sciences (India), 2019)
Introduction Use of topical fluorides in dentifrices has always been an important tool in prevention of dental caries in young children. Due to the easy availability of various low and high fluoride dentifrices, the parents have no clear understanding about their correct age-appropriate use in children. This study was undertaken to evaluate and understand the trend and current practices among the end user.Materials and Methods A total of 173 children aged 4 to 6 years were enrolled in the study from schools located in two different geographical areas of the Chandigarh city; group 1 (n = 90) from a peri-urban slum cluster: (Govt. Primary School, Indira Colony, Mani Majra, n = 51); Govt. Middle School, Mani Majra (n = 39); group 2 (n = 83) from an urban private city school (Ankur, Punjab University, Sector 14) using cluster sampling method. Two examiners using type IV examination examined all the children aged 4 to 6 years present using a preinstructed close-ended questionnaire. Data were analyzed using SPSS Software Version 25 (SPSS Inc., Chicago, IL, United States).Results The data regarding the knowledge of fluoride in pastes showed that 85% of the children were using high fluoride pastes, 10% were using nonfluoride pastes, and 5% were using low fluoride pastes. In group 1, none of the users were aware about the benefits/risk of using fluoride toothpastes and only 22% were aware in group 2. Only 27% of children in group 1 dispensed the correct amount of dentifrice for this age group i.e., a pea head size versus 67% in group 2; a half brush length was dispensed by 61.5% in group 1 and 28% in group 2, and just a smudge by 11.5% in group 1 and 5% in group 2. Forty one percent children in both the groups had a history of having intentionally consumed the toothpaste. The toothpaste was dispensed to the child by parent in 89% of cases in group 2 and only 50% in group 1 and 88% parents claimed to always supervise the child while tooth brushing versus only 53% in group 1. Majority of the respondents’, i.e., 97% in group 1 and 63% in group 2 had never been explained about the correct method of use of fluoride paste in children.Conclusion Knowledge about fluoridated toothpastes is low among the population. The children in peri-urban slums areas are exposed to the high fluoride pastes from very early in life and there is no other toothpaste which is brought home except for those which are commonly used among the members. In the city schools; however, a small percentage of population uses low fluoride pastes in children, possibly due to a greater awareness and access to information, but has no clear idea about their limitations and benefits of age-appropriate use. Till appropriate guidelines are available for the country, a safe practice to follow is tailoring individual need based protocol. The children in peri-urban slums areas need to be educated more on the health practices and importance of use of fluoride dentifrices and the children in the city schools need to be guided more on the age appropriate use of high and low fluoride dentifrices.
Keywords: fluoride dentifrices use; very young children; trend